Deep Infiltrating Endometriosis: Diagnostic Accuracy of Preoperative Magnetic Resonance Imaging with Respect to Morphological Criteria - Sebastian Harth; Fritz C. Roller; Felix Zeppernick; Ivo Meinhold-Heerlein; Gabriele A. Krombach (Diagnostics, 2023)
Several current guidelines recommend imaging in the diagnostic work-up of deep infiltrating endometriosis (DIE). The purpose of this retrospective diagnostic test study was to evaluate the diagnostic accuracy of MRI compared to laparoscopy for the identification of pelvic DIE, considering lesion morphology using MRI. In all, 160 consecutive patients were included who received pelvic MRI for evaluation of endometriosis between October 2018 and December 2020 and underwent subsequent laparoscopy within 12 months of the MRI examination. MRI findings were categorized for suspected DIE using the Enzian classification and were additionally graded using a newly suggested deep infiltrating endometriosis morphology score (DEMS). Endometriosis was diagnosed in 108 patients (all types, i.e., purely superficial and DIE), of which 88 cases were diagnosed with DIE and 20 with solely superficial peritoneal endometriosis (i.e., not deep infiltrating endometriosis/DIE). The overall positive and negative predictive values of MRI for the diagnosis of DIE, including lesions with assumed low and medium certainty of DIE on MRI (DEMS 1–3), were 84.3% (95% CI: 75.3–90.4) and 67.8% (95% CI: 60.6–74.2), respectively, and 100.0% and 59.0% (95% CI: 54.6–63.3) when strict MRI diagnostic criteria were applied (DEMS 3). Overall sensitivity of MRI was 67.0% (95% CI: 56.2–76.7), specificity was 84.7% (95% CI: 74.3–92.1), accuracy was 75.0% (95% CI: 67.6–81.5), positive likelihood ratio (LR+) was 4.39 (95% CI: 2.50–7.71), negative likelihood ratio (LR-) was 0.39 (95% CI: 0.28–0.53), and Cohen’s kappa was 0.51 (95% CI: 0.38–0.64). When strict reporting criteria are applied, MRI can serve as a method to confirm clinically suspected DIE.